Analisis Penggunaan Flash Card dalam Mengenalkan Anggota Tubuh Manusia Pada Anak Tunagrahita - Firdaus, Zuhairina; Aminah, Siti; Ruby, Arcivid Chorynia (Peneliti.net, 2025)
The objective of this study is to analyze the use of flash cards in an effort to introduce human body parts to children with intellectual disabilities at SLB Negeri Cendono Kudus. This type of research uses a qualitative method through a case study approach. The data collection techniques in this study include interviews, observations, and photo documentation. The subject of this research is subject R, a fourth-grade student at SLB diagnosed with a low level of intellectual disability. This research employs data analysis techniques consisting of data collection, data reduction, data presentation, and verification. Based on the results of this study, it can be concluded that using flash card media shows the subject's interest in naming human body parts, although it is still imperfect and requires assistance from others. The use of attractive pictorial flash cards also results in the subject responding positively to the ongoing learning process. Additionally, the use of flash card media in teaching children with intellectual disabilities must be done repeatedly to help the subject better remember the names of human body parts.